Planktonic foraminifers from sediments of the southeastern Okhotsk Sea (the last 20000 years). - Chekhovskaya, Maria P; Basov, Ivan A (PANGAEA, 1999)
Based on analyses of taxonomic composition of planktonic foraminifera and oxygen isotopic composition of their shells in the sediment core V34-90 from the eastern slope of the USSR Academy of Sciences Rise in the southeast Sea of Okhotsk the main climatic and hydrological variations over the past 20 Ka have been traced and dated by the radiocarbon method. The followed periods have been revealed: glacial (20-12.5 Ka), deglaciation (12.5-8.0 Ka) with a pronounced cooling event (Late Drias about 10.8 Ka) and post deglaciation (last 8.0 Ka).
Isotope age and relative abundance of planktonic foraminifera in Core Vulk-34-90, Sea of Okhotsk
Keywords: Age, 14C conventional; Age, dated; Archive of Ocean Data; ARCOD; Counting, foraminifera, planktic; DEPTH, sediment/rock; Foraminifera, planktic; GC; Globigerina bulloides; Globigerina glutinata; Globigerina quinqueloba; Globigerina scitula; Globigerinita uvula; Gravity corer; Neogloboquadrina pachyderma dextral; Neogloboquadrina pachyderma sinistral; Sea of Okhotsk; Vulk-34-90